2009
DOI: 10.1186/1471-2164-10-357
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics in chicken and Pekin duck using FISH mapping and microarray analysis

Abstract: BackgroundThe availability of the complete chicken (Gallus gallus) genome sequence as well as a large number of chicken probes for fluorescent in-situ hybridization (FISH) and microarray resources facilitate comparative genomic studies between chicken and other bird species. In a previous study, we provided a comprehensive cytogenetic map for the turkey (Meleagris gallopavo) and the first analysis of copy number variants (CNVs) in birds. Here, we extend this approach to the Pekin duck (Anas platyrhynchos), an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
94
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 38 publications
10
94
1
4
Order By: Relevance
“…Although the chromosomal rearrangement between GGA3 and CCO3 we identified should be considered as a pericentric inversion, an independent event, namely centromere repositioning to a different genetic location, must have driven the change of chromosome morphology. De novo centromere formation has been earlier proposed for chromosome 4 in red-legged partridge (Kasai et al 2003) and chromosome Z in Pekin duck as compare with chicken orthologs (Skinner et al 2009). The centromere repositioning during karyotype evolution, the so-called evolutionary new centromere (ENC) formation, is rather a common phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the chromosomal rearrangement between GGA3 and CCO3 we identified should be considered as a pericentric inversion, an independent event, namely centromere repositioning to a different genetic location, must have driven the change of chromosome morphology. De novo centromere formation has been earlier proposed for chromosome 4 in red-legged partridge (Kasai et al 2003) and chromosome Z in Pekin duck as compare with chicken orthologs (Skinner et al 2009). The centromere repositioning during karyotype evolution, the so-called evolutionary new centromere (ENC) formation, is rather a common phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The centromere repositioning during karyotype evolution, the so-called evolutionary new centromere (ENC) formation, is rather a common phenomenon. It has been repeatedly described in different taxonomic groups as diverged as mammals, birds, and plants (Kasai et al 2003;Nagaki et al 2004;O'Neill et al 2004;Galkina et al 2006;Han et al 2009;Skinner et al 2009;Rocchi et al 2012). Though mechanisms of ENC formation are obscure, an attractive hypothesis implies the following events: old centromere inactivation and neocentromere formation in a new euchromatic locus, with fixation of these first steps in population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have found CNVs related to various human diseases (Wain et al 2009;Zhang et al 2009;Stankiewicz and Lupski 2010). CNVs are also observed in Aves both in inter-and intraspecies (Griffin et al 2008;Skinner et al 2009;Völker et al 2010;Wang et al 2010). In addition, an association between CNVs and Figure 3 Genetic (left) and physical (right) maps of Fm on chicken chromosome 20.…”
Section: Discussionmentioning
confidence: 99%
“…Between 2004 and 2010 the chicken genome was the only avian representative being completely characterized and karyotyped (Hillier et al, 2004;Masabanda et al, 2004), but this nevertheless has allowed cross-species chromosome painting to numerous other birds (reviewed in Griffin et al, 2007) and BAC mapping to build physical maps of a few others. These include turkey, duck and zebra finch Skinner et al, 2009a;Volker et al, 2010). From these studies, a number of key messages emerge: first, chicken chromosomes 1-3 and 5-10+Z are representative of the ancestral pattern.…”
Section: Introductionmentioning
confidence: 99%